The item position effects in international examinations: the roles of gender - Sideridis, Georgios; Hamed, Hailah; Jaffari, Fathima (Frontiers in Psychology, 2023)
The goal of the present study was to evaluate the roles of item position in terms of item difficulty levels in the assessment of aptitude. Using data from a National Examination in Saudi Arabia, the item position effect was evaluated as a teacher licensure test (GTLT) was administered using five different forms with the same items appearing in a different order. Results indicated minuscule in magnitude position effects estimates, overall, with initially 11.1% of the tests being significant but all of them failing to reach significance using the Holm-Bonferroni and Sidak corrective procedures. With regard to gender, item position effects emerged in 47.6% of the tests after adjusting the level of significance using the Sidak correction. Interestingly, the direction of effect was consistent so that in 87% of the significant gender comparisons, item position effects were in the direction where females were spending more time on items when they appeared in later positions on the test compared to males. Assuming that items appearing later on the test are likely more difficult, the present findings suggest a profile of deep processing and active engagement in females when facing achievement tests.